2013
DOI: 10.3109/00365548.2013.844350
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of infections with carbapenem-resistant Gram-negative bacteria treated with polymyxin B-based combination therapy

Abstract: CRGNB infections are associated with previous antibiotic and health care exposure. Mortality is related to age and the severity of chronic and acute illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…One study, which employed colistin combinations in Gram-negative infections, found no difference between treatment regimens, but found mortality was significantly associated with age, CCI score and severity of acute disease. [28] Similar to the present study, other researchers have found higher mortality in patients with malignancy and chronic renal damage. [4] Colistin-related nephrotoxicity rates varying between 0 and 33% have been reported in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…One study, which employed colistin combinations in Gram-negative infections, found no difference between treatment regimens, but found mortality was significantly associated with age, CCI score and severity of acute disease. [28] Similar to the present study, other researchers have found higher mortality in patients with malignancy and chronic renal damage. [4] Colistin-related nephrotoxicity rates varying between 0 and 33% have been reported in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Large, prospective, randomized trials are necessary to establish the benefits with optimal dosage selection [38]. In an observational cohort study, Crusio et al [45] evaluated different polymyxin B combination therapies in carbapenem-resistant Gram-negative bacteria. Different infections included A. baumannii ( n = 34/104), K. pneumoniae ( n = 25/104), P. aeruginosa ( n = 11/104), and multiple organisms ( n = 34/105).…”
Section: Efficacy Of Polymyxin B: Combination Therapymentioning
confidence: 99%
“…A study including 104 patients with carbapenem-resistant (CR) bacterial infection indicated polymyxin B combination therapy with all-cause mortality of 47% during hospitalization and 77% after 6 months (46). Is combination therapy better than monotherapy?…”
Section: Combination Therapymentioning
confidence: 99%
“…Toxicities associated with colistin do not appear to increase with use of a loading dose (38,46). Limited clinical evidence is available.…”
Section: Loading Dosesmentioning
confidence: 99%
See 1 more Smart Citation